The Effect of Business Cycle, Income Diversification, and Financial Ratios on Bank Risk in the ASEAN Region - Ridho Sahputra, Muhammad; Adam , Mohamad; Muizzuddin; Isnurhadi (Journal of Business and Management Review, 2024)
Research Aims: This research aims to analyze the influence of the business cycle, income diversification, and financial ratios as proxied by profitability and liquidity on the level of banking risk adjustment in ASEAN in the 2020-2022 period. Design/methodology/approach: The research used a sample of 93 banks in the ASEAN region. Sample selection applied purposive sampling techniques based on certain criteria in the Philippines, Indonesia, Malaysia, Singapore, Thailand and Vietnam. The estimation technique used is the Ordinary Least Square method on panel data to analyze the model being built. Research Findings: Research shows that the relationship between the business cycle and bank risk is negative. This means that when the economy is in a contraction phase, bank risk will decrease and vice versa. Then, banks that diversify their income can reduce bank risk. On the other hand, the influence of profitability and liquidity has a negative effect, meaning that a high level of income accompanied by liquid bank assets has the potential to reduce the level of bank risk. Apart from that, there are several other aspects that banks need to pay attention to in anticipating emerging risks, including previous year's credit risk, business size, loan loss reserves, asset growth and financial freedom. Theoretical Contribution/Originality: The originality of the research lies in its comprehensive approach to analyzing the impact of business cycles, income diversification, and financial ratios on bank risk in the ASEAN region. The study's methodology, variables, and empirical evidence all contribute to its originality and relevance to the existing literature Keywords: Revenue Diversification, Liquidity, Profitability, Bank Risk, Business Cycle